Does the source of fundamental data matter? - Ondrej Tobek; Martin Hronec (Charles University in Prague, Institute of Economic Studies (IES), 2018)
We study the role of the choice of a fundamental database on the portfolio returns of a set of 74 fundamental anomalies. We benchmark Compustat by comparing it to Datastream in the US and find systematic differences in the raw financial statements across the databases. These differences only have a small effect on the returns of anomalies when they are constructed on stock-months existing in both databases. Different stock coverage across the databases, however, leads to large statistically and economically significant disparities in the returns. Profitability anomalies yield negative returns on the Datastream universe.
Keywords: G11; G12; G15; 330